Management of Peri‐Implant Soft Tissue Dehiscence Using Laterally Closed Tunneling With a Connective Tissue Graft: A Case Report - Hisham Tarek (Clinical Case Reports, 2026)
ABSTRACT Peri‐implant soft tissue dehiscence is an esthetic complication for which coronally advanced flap with connective tissue grafting remains a predictable treatment, whereas evidence for laterally closed tunneling (LCT) around implants is limited. This single‐patient case report describes a 4 × 3 mm labial peri‐implant soft tissue dehiscence at an immediately placed implant replacing the maxillary left central incisor. LCT combined with a de‐epithelialized free gingival graft and limited implantoplasty was performed. At 24 months, complete coverage was maintained; buccal soft tissue thickness increased from 1.0 to 2.7 mm, keratinized tissue width from 1 to 3 mm, Pink Esthetic Score from 6 to 12, Mucosal Scarring Index from 3 to 0, and patient satisfaction from 4 to 10. Standardized periapical radiographs showed stable interproximal crestal bone levels without evidence of progressive bone loss. In this single case, LCT with a de‐epithelialized free gingival graft was associated with stable soft tissue coverage and favorable esthetic and patient‐reported outcomes over 24 months; further studies are required to determine reproducibility and predictability.